Digital business process integration and sustainability among smes: the mediating role of operational efficiency and the moderating role of credit access - Dedrix Stephenson Bindeeba; Susan Atuhaire; Rennie Bakashaba; Eddy Kurobuza Tukamushaba (Journal of Sustainable Business, 2025)
This study investigates the impact of digital business process integration on economic performance and environmental performance among small and medium-sized enterprises in Uganda, a resource‐constrained context. It examines operational efficiency as a mediating mechanism and access to credit as a moderating factor. Drawing on the Resource-Based View and Dynamic Capabilities Theory, the research highlights how integrated digital processes and financial support jointly influence the sustainability and competitiveness of these enterprises. Data were collected from 228 enterprises via a structured survey and analyzed using covariance-based structural equation modeling in AMOS. Bootstrapping procedures tested indirect effects, and a multi-group analysis evaluated the moderating role of credit access. The results show that digital business process integration significantly improves both economic and environmental outcomes, with operational efficiency partially mediating these effects by enhancing workflow speed, optimizing resource use, and reducing errors. Furthermore, enterprises with access to credit experience greater operational and financial benefits from digital integration, whereas those without credit rely more heavily on operational efficiency to achieve environmental goals. These findings underscore the importance of robust digital infrastructure, process optimization, and inclusive financing in promoting sustainable development among small and medium-sized enterprises. The study offers actionable recommendations for policymakers and managers aiming to foster digital adoption and resource efficiency in low-income economies.
Keywords: Digital business process integration; Operational efficiency; Economic performance; Environmental performance; Credit access